THE ROLE OF FOREIGN DIRECT INVESTMENT IN ECONOMIC DEVELOPMENT: THE CASE OF IRAQ - Marwa Hassan Hadi (Scholar Express Journals, 2023)
The success of the Iraqi economy has created a leader in all that it offers at all levels, especially economics based on three characteristics: options in a large amount of diverse irrigation that is allocated to you, a wide-ranging market, and the presence of a relatively large and educated young population. Many of the most important properties of the Iraqi economy benefit from it, as Iraq is a rentier country that possesses huge wealth in the field of oil. Iraq possesses the third largest reserve of crude oil in the world, in addition to the presence of other minerals that enhance this huge wealth. Iraq also possesses the world and associated gas, as well as a large market that attracts goods and services from all countries, especially neighboring countries or countries whose export values have increased, especially after a year. 2003, as we note the openness of the Iraqi market to a large extent to goods imported from it, and this in itself constitutes a pillar and basis for attracting investment
Keywords: Role; Foreign; Direct Investment